Speech act analysis of David Mamet’s American Buffalo - Firdaus Sleman Hamad; Suhayla H. Majeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Speech act is the usage of words and sentences that commits the speaker or the hearer to do something. Searle group’s speech acts into five categories, which are assertives, directives, commisives, expressives and declarativies. This paper aims at analyzing the categories of speech acts in the play ‘ American buffalo’ by david mamet.it aims to find the types and the functions of the speech acts and the difference between them.This is done through analyzing four texts of the characters’ dialogues.through which we can understand the sophisticated personalities of the different characters. The analysis is carried out from a pragmatic point of view, mainly on the basis of the typology prposed by Searle (1969).